Religion's Imperial Pasts, Global Futures Twitter Storify export - Strauber, Chris (Tufts Archival Research Center, 2017)
PDF export of a Storify created from tweets sent during a lecture by David Chidester entitled "Empire of Religion," part of the Melon Sawyer Seminar in Global Humanities.